SEISMIC NOISE AND TEMPORARY SEISMOLOGICAL MEASUREMENTS IN THE POSTOJNA CAVE SYSTEM - Živčić, Mladen; Costa, Giovanni; Suhadolc, Peter; Šebela, Stanka (Acta Carsologica, 2014)
Karst caves are suitable places for seismological measurements because they are situated under the surface and often have lower seismic noise than locations on the surface. The idea to establish the first underground seismological station in Slovenia has led us to make preliminary seismic noise measurements in Črna Jama (part of the Postojna Cave System) in 2007. In search for further suitable stable places within the cave, we next performed seismic noise measurements, followed by a temporary accelerometer installation, near the highest point of the Velika Gora chamber in the first half of 2010. Since 7 May 2010, the seismic station is located inside the 9 m long artificial tunnel that was built for geophysical measurement purposes in Tartarus passage in 1931. From 27 January to 12 February 2010, the seismological station Velika Gora in Postojna Cave System (VGPJ) recorded 79 earthquakes with epicenters near Postojna. Records were especially important to determine the seismological characteristics of the MLV=3.7 Postojna earthquake (15 January 2010) aftershocks. The station in the Tartarus tunnel (TTPJ) operated from 7 May 2010 till 21 December 2010 and recorded more than hundred earthquakes of the sequence near Ilirska Bistrica that started on 15 September 2010, with two MLV=3.5 earthquakes and lasted till the end of the year 2010. The aim of this study is the installation of a permanent seismic station inside the Postojna Cave System and future real-time integration of the related seismological data within the Slovenian and Italian seismological networks.